Gas Flaring and its Socioeconomic Implications for Rural Communities in Kurdistan Region of Iraq (KRI): Reflections on the Impact of Gas Flaring in Tawke Community - Agbonifo, Philip E.; Shafeeq, Omed; Abdal, Guhdar; Bhatti, Uzair (Journal of Ecohumanism, 2024)
The study critically examines the problem of gas flaring and its socioeconomic implications in the KRI with emphasis on Tawke community who are predominantly peasant rural farmers. For several decades, KRI allowed natural gas to be flared which poses severe challenges to health, agricultural productivity and the environment with huge socioeconomic dimension to the survival of the local population. Although Iraq has sizeable natural gas reserves, however, about 70% of natural gas produced are flared which is responsible for more than 20 million tons of CO2 emissions annually that cost the domestic economy billions of dollars in lost revenue and other consequences including threat to public health and the environment. Thus, the study conducted simple narrative and in-depth qualitative in-person interview with some employees of DNO, public sector workers and members of the Tawke community on the impact and socioeconomic implications of gas flaring on their livelihood. The research findings resonate and lend credence to the widely held views on the state of the environment in KRI and revealed severe environmental consequences, health consequences, low yields in agriculture with socioeconomic and cultural implications on livelihood of the local people particularly Tawke community.